Benzylphenylpyrrolizinones with Anti‐amyloid and Radical Scavenging Effects, Potentially Useful in Alzheimer's Disease Treatment. (12th April 2017) - Jourdan, Jean‐Pierre; Since, Marc; El Kihel, Laïla; Lecoutey, Cédric; Corvaisier, Sophie; Legay, Rémi; Sopková‐de Oliveira Santos, Jana; Cresteil, Thierry; Malzert‐Fréon, Aurélie; Rochais, Christophe; Dallemagne, Patrick
Abstract: Herein we describe the drug design steps developed to increase the radical scavenging and β‐amyloid aggregation inhibitory activities of a previously described series of benzylidenephenylpyrrolizinones. Among the newly synthesized derivatives, some benzylphenylpyrrolizinones exhibited interesting results in regard to those activities. Initial druggability parameters were measured, and suggest these compounds as a suitable starting point for potential alternatives in treating Alzheimer's disease. Abstract : Pick up & break up : This study aimed at increasing the radical scavenging and anti‐Aβ‐aggregation activities of a series of benzylidenephenylpyrrolizinones. Some of the new derivatives showed promising results in this regard. These compounds could serve as a good starting point for new drugs to treat Alzheimer's disease.